PENGARUH APLIKASI LECTORA INSPIRE BERBASIS ICT SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MATA DIKLAT SOD TERHADAP HASIL BELAJAR SISWA KELAS X JURUSAN TEKNIK KOMPUTER JARINGAN SMKN 1 TANJUANG BARU - Anggi Hadi Wijaya; Legiman Slamet; Dharma Liza Said (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research aims to known the positive and significance influence of the Interactive learning media instructionusing Lectora Inspire based ICTof students class X TKJ SMKN 1Tanjuang Baru. This type of research is descriptive quantitative which using true eksperiment. Selection’s techniques of the informantin this research using simply random sampling which class X TKJ 1A as a class of control without Lectora Inspire aplication instruction in study and class X TKJ 1B as a class of eksperimen with interactive Lectora Inspire aplication. Data collection techniquesusing post test of the student’s examination at each meeting. Data were analyzed by used the statistical methods of normality, homogenenity, and hyphotesis. The results of data analysis showed : 1 ) Hyphotesis that tested by using t-test show that Ho refused and Hi accepted. This mean that interactive multimedia instruction has positive significance effect to learning achievement of the students of SMKN 1 Tanjuang Baru, 2 ) Learning achievement students of eksperiment class is higher than students of control class , 3 ) the percentage of the influence effect are 11% Keywords : influence, Interactive learning media instructionusing Lectora Inspire based ICT